Henoch-Schonlein Purpura with multiple renal calculi with hydronephrosis-A Case Report - Kriti Mohan; Swathi Chacham; Ajay Bharti; Balram Ji Omar (Open Journal of Tropical Medicine - Peertechz Publications, 2020)
Henoch-Scholein Purpura (HSP) is one of the most common vasculitic disorder of childhood and is characterised by the presence of nonthrombocytopenic purpura (and usually) palpable purpura, transient arthralgia (occasionally arthritis), abdominal symptoms and renal involvement. Here we are reporting a previously healthy adolescent male child who presented with skin, joint and gastrointestinal manifestations of HSP as well as coincidental finding of multiple calculi in right kidney causing obstructive hydronephrosis on ultrasonography. Renal calculi with HSP can be a coincidental finding but it can create diagnostic dilemma on clinical and laboratory grounds especially due to abdominal colic and other renal manifestations. So we tried to bring this case into light because this dilemma may be responsible for sufferings for the patient without timely diagnosis and treatment.